Orbital Lymphoma Masquerading as Panuveitis - Panda, Puneet (2010)
PURPOSE: To describe a case of orbital mucosa-associated lymphoid tissue (MALT) lymphoma masquerading as unilateral panuveitis. METHODS: Retrospective chart review. RESULTS: A 53-year-old female patient with unilateral vitritis and exudative retinal detachment refractory to immunosuppressive treatment was eventually diagnosed with orbital MALT lymphoma. Following treatment with radiotherapy and rituximab, the patient's intraocular inflammation and retinal detachment resolved. CONCLUSIONS: Orbital MALT lymphoma can masquerade as refractory unilateral panuveitis with exudative retinal detachment and appears to respond to a combination of radiotherapy and specific B-cell-targeted systemic therapy.